MANAJEMEN PEMBELAJARAN OUTDOOR MELAUI PERMAINAN EDUKATIF UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI (STUDI KASUS DI TK IT BINTANG RAYA) - Emay Mastiani; Maman Suherman; Susi Susanti; Asep Fauzi Amanu; Neneng Purwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of gross motor skills in early childhood needs to be stimulated through enjoyable and well-directed learning activities. However, preliminary observations at TK IT Bintang Raya Cicalengka indicated that some children still experience difficulties in basic motor movements such as jumping, maintaining balance, and coordinating body movements. This study aims to describe the management of learning based on educational games in improving early childhood gross motor skills through the PDCA (Plan–Do–Check–Act) cycle approach. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. This study is grounded in theories of early childhood motor development and the concept of continuous improvement through the PDCA cycle in learning management. The results show that the implementation of educational games such as line jumping, ball throwing and catching, walking on balance boards, and simple obstacle games can enhance muscle strength, balance, coordination, and agility in children. Based on these findings, it can be concluded that educational game-based learning management using the PDCA approach is effective in improving gross motor skills of early childhood students at TK IT Bintang Raya Cicalengka.